H-mode plasmas in the pre-fusion power operation 1 phase of the ITER research plan. (9th June 2021) - Loarte, A.; Polevoi, A.R.; Schneider, M.; Pinches, S.D.; Fable, E.; Militello Asp, E.; Baranov, Y.; Casson, F.; Corrigan, G.; Garzotti, L.; Harting, D.; Knight, P.; et al.
Abstract: The optimum conditions for access to and sustainment of H -mode plasmas and their expected plasma parameters in the pre-fusion power operation 1 (PFPO-1) phase of the ITER research plan, where the additional plasma heating will be provided by 20 MW of electron cyclotron heating, are assessed in order to identify key open R&D issues. The assessment is performed on the basis of empirical and physics-based scalings derived from present experiments and integrated modelling of these plasmas including a range of first-principle transport models for the core plasma. The predictions of the integrated modelling of ITER H -mode plasmas are compared with ITER-relevant experiments carried out at JET (low-collisionality high-current H modes) and ASDEX Upgrade (significant electron heating) for both global H -mode properties and scale lengths of density and temperature profiles finding reasonable agreement. Specific integration issues of the PFPO-1 H -mode plasma scenarios are discussed taking into account the impact of the specificities of the ITER tokamak design (level of ripple, etc).